Age distribution of antibodies to animal influenza A viruses in human sera - Gorbunova, A. S. (1968)
A total of 394 sera from persons in different age-groups among the inhabitants of the Vladivostok area were studied by the haemagglutination-inhibition (HI) test for the presence of influenza antibodies. Each serum was examined against 12 antigens of influenza A virus of human (A0, A1, and 2 strains of A2) and animal (1 swine, 2 equine and 5 avian strains) origin. All the sera were collected 8-9 months after the outbreak of A2 influenza in 1965. Antibodies to some animal viruses were present: Swine/Iowa, Equi/2/Miami, Tern/South Africa and Chicken/Scotland strains; negative results were found to Equi/1/Prague, Duck/England and Duck/Czechoslovakia and fowl plague strains. The pattern of HI antibody distribution to animal strains showed an increase in the range in relation to age; the largest was found in the older age-group (70 years and over). The authors suggest that antibodies in the human sera to animal strains are not necessarily an indication of past infection with those strains.